1999
DOI: 10.1021/ic991195i
|View full text |Cite
|
Sign up to set email alerts
|

Highly Emissive Hexanuclear Rhenium(III) Clusters Containing the Cubic Cores [Re6S8]2+and [Re6Se8]2+

Abstract: Clusters based on the cubic, hexanuclear rhenium(III) core [Re6(μ3-Q)8]2+ (Q = S, Se) emit red phosphorescence with microsecond-scale lifetimes. Emission quantum yields of 16 clusters range from 1% to 23%; those having O-bound terminal ligands feature the highest yields and the longest liftimes. Certain clusters are photolabile, with medium-sensitive emissive properties. When photodecomplexation is suppressed, all clusters herein obey the energy gap law, indicating excitation confined to the [Re6Q8]2+ core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
77
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 25 publications
8
77
0
Order By: Relevance
“…Indeed, their superior synthetic utilities have been demonstrated through the preparation of a great variety of molecular and supramolecular architectures. [5,[9][10][11] The use of the clusters in such developments, however, has been largely structural rather than functional, [12][13][14] and fundamentally new chemistry supported by the cluster core is conspicuously lacking.…”
Section: A C H T U N G T R E N N U N G (Pet 3 ) N a C H T U N G T R Ementioning
confidence: 99%
“…Indeed, their superior synthetic utilities have been demonstrated through the preparation of a great variety of molecular and supramolecular architectures. [5,[9][10][11] The use of the clusters in such developments, however, has been largely structural rather than functional, [12][13][14] and fundamentally new chemistry supported by the cluster core is conspicuously lacking.…”
Section: A C H T U N G T R E N N U N G (Pet 3 ) N a C H T U N G T R Ementioning
confidence: 99%
“…We reported previously, on the other hand, that hexarhenium(III) clusters, [Re 6 (l 3 -S) 8 X 6 ] 4-(X = Cl -, Br -, I -, and so forth), showed relatively intense room temperature emission in the visible * near infrared region (600-1,000 nm) with the emission lifetime (s) and quantum yield (U) in acetonitrile being s = 4-11 ls and U = 0.015-0.056, respectively [8] [15], N-heteroaromatics [16][17][18][19][20][21], phosphine derivatives [17,18,22,23], HCOO [24], CH3COO [25], and N 3 [26] [8,29]. Acetonitrile (Wako Pure Chemicals Co. Ltd.) as a medium throughout the study was purified by distillation over CaH 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting aspect of octahedral rhenium cluster complexes is their potential for photodynamic therapy (PDT) which is based on the excitation properties of a photosensitizer by visible or near-infrared light of a specific wavelength [7,8]. Recent studies showed that many octahedral rhenium cluster complexes both in solution [9][10][11][12][13][14][15][16][17][18][19][20][21] and in solid state [16,18,22] display photoluminescence just in the spectra region where PDT is effective. Thus, similar complexes can be considered as a novel class of potential photosensitizers for PDT.…”
Section: Introductionmentioning
confidence: 99%